Altering Antigen Charge to Control Self-Assembly and Processing of Immune Signals During Cancer Vaccination - Tsai, Shannon J.; Amerman, Allie; Jewell, Christopher M. (Frontiers in Immunology, 2021)
Biomaterial delivery systems offer unique potential to improve cancer vaccines by offering targeted delivery and modularity to address disease heterogeneity. Here, we develop a simple platform using a conserved human melanoma peptide antigen (Trp2) modified with cationic arginine residues that condenses an anionic toll-like receptor agonist (TLRa), CpG, into polyplex-like nanoparticles. We reasoned that these structures could offer several useful features for immunotherapy – such as tunable loading, co-delivery of immune cues, and cargo protection – while eliminating the need for synthetic polymers or other complicating delivery systems. We demonstrate that Trp2/CpG polyplexes can readily form over a range of Trp2:CpG ratios and improve antigen uptake by primary antigen presenting cells. We show antigen loading can be tuned by interchanging Trp2 peptides with defined charges and numbers of arginine residues. Notably, these polyplexes with greater antigen loading enhance the functionality of Trp-2 specific T cells and in a mouse melanoma model, decrease tumor burden and improve survival. This work highlights opportunities to control the biophysical properties of nanostructured materials built from immune signals to enhance immunotherapy, without the added complexity or background immune effects often associated with synthetic carriers.